CTT532 : Bio mechanics for actor / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course aims to expose students to identify the basic figural movements through physical action processes, characterizations and stage compositions. Physical theatre focuses on expressions of movements, skeletal and muscular systems, and body strengths to enable students to perform creatively.